Dracunculiasis of the Breast: Radiological Manifestations of a Rare Disease - Barry, Shannon K. (EduRad, 2012)
Dracunculiasis of the breast is a rare manifestation of prior infection with the parasite dracunculus medinensis (guinea worm). We describe a case of a 60- year-old woman, who had recently emigrated from Cameroon. She presented for an annual screening mammogram and was found to have coarse linear or coiled serpiginous calcifications. These findings were recognized as calcified guinea worms within the breast tissue. This case report aims to highlight the mammographic findings of this rare infectious disease.